Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae) - Sinclair, Bradley J.; Plant, Adrian R. (Zootaxa, 2017)
Seven new species of Dolichocephala Macquart from Thailand are described (D. bicolor sp. nov., D. curvata sp. nov., D. immaculata sp. nov., D. incus sp. nov., D. longicerca sp. nov., D. srisukai sp. nov., D. thailandensis sp. nov.). A key to species is provided, distributions mapped and phenology and biogeography discussed.